The Impact Of Covid-19 Pandemic On Family Psychological Resistance In Couples Of Reproductive Age - gustina, Irwanti - (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Family resilience is the main element in facing vulnerability to external shocks, both small, medium and large shocks. PandemicCovid-19 that hit the world, especially Indonesia since January 2019, was a big shock that in a short time turned the world towards damage, death, economic destruction, panic, chaos and even divorce cases. Another impact of these conditions affects the psychological resilience of the family. This research is a quantitative research by designCross-Sectional which aims to find out the Relationship between the Impact of the Covid-19 Pandemic on Family Psychological Resilience with the object of couples of reproductive agein Cipayung Village, East Jakarta. The number of samples used in this study was 50 respondents. Based on the results of the chi-square test,  p value of ≤ 0.05 was obtained, which means that there is significant relationship between the Number of Children and work variables on family psychological resilience in Couples of Reproductive Age affected by the Covid-19 pandemic in Cipayung Village, East Jakarta in 2022.Keywords: family psychological resistance; covid pandemic; couples of childbearing age.